Epidemiologic Analysis of Gastric Carcinoma in the Western Region of Nepal (Nepal Journal of Epidemiology, 2010)
BackgroundGastric cancer is among the most common malignancies in Asia, comprising 74% of all global cases. Identifying the environmental risk factors may possibly shed more light on effective treatment and the prevention of this disease. The aim of our study is to document  different histologic types of gastric cancer as per age, sex and ethnic groups in the patients in Nepal, to know the frequency of different gross and microscopic subtypes (according to Lauren's classification) of tumor and to find out the association of H. pylori and other major risk factors with gastric cancer.Materials and Methods  The present study is a hospital based retrospective study done in the Department of Pathology, Manipal Teaching Hospital, Pokhara, Nepal, from Jan 1999 to July 2010. All the endoscopic biopsies and gastrectomy specimens from patients with diagnosed gastric carcinoma were reviewed and the clinical and other data were analyzed.ResultsIn this study period, a total of 1223 cases related to stomach were received in Department of Pathology. Considering the inclusion and exclusion criteria, a total of 397 cases - 315 cases of endoscopic biopsy and 82 cases of gastrectomy - were included in the study. In our study, the most affected age group and caste were 61-70 years ( 47.36%, CI 42.44% to 52.27%) and Gurungs (32%, CI 27.16% to 36.32%). The commonest gross and microscopic types were Borrmann's type IV (40%, CI 29.63% to 50.86%) and intestinal type (53%, CI 47.99% to 57.81%). Gastric antrum was the most affected site (70%, CI 65.26% to 74.29%). Among the cases with H pylori, antrum (62.5% CI 45.73% to 79.27%) was found to be the commonest site. Among all cases in Gurung, Chhetri and Brahmin communities, we retrieved data regarding risk factors in 93, 65 and 50 cases respectively. Significant relationship was found between the three risk factors studied and the ethnic groups. Smoked meat and alcohol were found to be associated with gastric carcinoma more in Gurungs and Chhetris than in Brahmins (p= 0.0001). On the contrary, cases among Brahmins are found to more associated with smoking than Gurungs and Chhetris (p= 0.0001).ConclusionGastric carcinoma is a common malignancy in this part of world. The most high risk group includes elderly males with history of alcoholism and smoked meat consumption in Gurung community and with history of smoking from Brahmin family. We advise that regular endoscopic surveillance should be done at least in high risk group for the early detection of cancer.Key Words: Gastric Carcinoma; Ethnicity; Risk Factors; Epidemiology; Helicobacter pylori; NepalDOI: 10.3126/nje.v1i1.4109Nepal Journal of Epidemiology 2010;1 (1):27-32